Biossensores eletroquímicos com acetilcolinesterase e produtos naturais para o controle de formigas cortadeiras - Silva, Gabriele Fernanda da (Universidade Federal de São Carlos, 2025)
Agriculture is an essential sector for the Brazilian economy but faces major challenges in pest control, such as leaf-cutting ants (Atta and Acromyrmex), which are responsible for significant losses in agricultural and forestry productivity. Although synthetic pesticides are still widely used, their side effects on human health, the environment, and non-target organisms drive the search for safer and more selective alternatives. In this work, disposable electrochemical biosensors were developed using acetylcholinesterase (AChE) enzymes extracted from leaf-cutting ants (AsAChE-A and AsAChE-B) and electric eel (EelAChE). The enzymes were immobilized on magnetic particles and applied to screen-printed carbon electrodes. The immobilization process was optimized with the aid of central composite design (CCD), allowing the determination of optimal conditions with 1.4 mg/mL of magnetic particles, 7 µg/mL of AChE, and an immobilization time of 30 minutes. The constructed biosensors demonstrated sensitivity toward the specific inhibitor malathion. The limits of detection (LOD) were 2.6 nM for AsAChE-A and 14 nM for AsAChE-B. These results reinforce the applicability of native enzymes from leaf-cutting ants in analytical devices for inhibitor screening, with potential for the development of selective and sustainable bioinsecticides. The sensors also showed sensitivity and selectivity toward galantamine, another anticholinesterase inhibitor, in addition to being applicable to the screening of microbial extracts associated with ant nests. This proposal proves promising as a tool for the identification of new bioinsecticidal compounds, contributing to more ecological and specific pest control with lower environmental impact.
Electrochemical biosensors with acetylcholinesterase and natural products for the control of leaf-cutting ants
Keywords: Formiga cortadeira; Biossensor eletroquímico; Acetilcolinesterase; Produtos naturais; Leaf-cutting; Electrochemical biosensors; Acetylcholinesterase; Natural products; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS; 2. Fome Zero e Agricultura Sustentável